2017
DOI: 10.1175/jhm-d-16-0199.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Noah Frozen Soil Parameterization for Application to a Tibetan Meadow Ecosystem

Abstract: This study evaluates the Noah land surface model (LSM) in its ability to simulate water and heat exchanges over frozen ground in a Tibetan meadow ecosystem. A comprehensive dataset including in situ micrometeorological and soil moisture-temperature profile measurements collected between November and March is utilized, and analyses of the measurements reveal that the measured soil freezing characteristics are better captured by 1) modifying the parameter b l implemented in the current Noah LSM that constrains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 56 publications
(63 reference statements)
2
52
0
3
Order By: Relevance
“…Similar results have also been demonstrated in other simulations, such as Zheng et al () simulated Maqu station using the NOAH model and Bao et al () simulation in a typical cold region in northwestern China using the HydroSib2 frozen soil model. There are different explanations for this phenomenon, such as the effect of snow and organic matter (Bao et al, ; Zheng et al, ). Additionally, the heat change in the soil introduced by thermal conductivity, heat capacity, and vapor transfer may affect the soil temperature, as discussed later.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results have also been demonstrated in other simulations, such as Zheng et al () simulated Maqu station using the NOAH model and Bao et al () simulation in a typical cold region in northwestern China using the HydroSib2 frozen soil model. There are different explanations for this phenomenon, such as the effect of snow and organic matter (Bao et al, ; Zheng et al, ). Additionally, the heat change in the soil introduced by thermal conductivity, heat capacity, and vapor transfer may affect the soil temperature, as discussed later.…”
Section: Resultssupporting
confidence: 87%
“…The average plant height is approximately 5 cm in the cold season and approximately 20 cm in the warm season. The soil starts freezing around the beginning of November and starts to thaw around the beginning of March (Zheng et al, ). Recently, continued warming has been observed in this region, which may lead to permafrost degradation, and both the frozen soil area and depth have decreased (Cheng & Wu, ; Wu et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil ice prominently affects the soil water and heat transport. Many studies (e.g., Decker & Zeng, ; Koren et al, ; Niu & Yang, ; Zheng et al, ) have discussed the effects of soil ice on relationship between soil liquid water and soil temperature (equation ). The relationship of soil hydrological and thermal states proposed by Koren et al () and Decker and Zeng () is gψsatLf1+ckθice2θliqθsatbTTfT=0 where c k = 8.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies (e.g., Niu & Yang, ) focused on the relationship between soil temperature and moisture in soil freezing process and have greatly improved it. However, some disagreements between model simulations and observations still exist; for example, study of Zheng et al () indicated that incorporating parameterizations of phase change from CLM (Oleson et al, ) into Noah‐MP (Yang et al, ) degraded the simulations of soil water during FT process. Analyzing and assessing FT parameterization in FT processes on different temporal scales can be useful for improving LSM performance.…”
Section: Introductionmentioning
confidence: 99%